Increase in 20–50 Hz (gamma frequencies) power spectrum and synchronization after chronic vagal nerve stimulation - Marrosu, F.; Santoni, F.; Puligheddu, M.; Barberini, L.; Maleci, A.; Ennas, F.; Mascia, M.; Zanetti, G.; Tuveri, A.; Biggio, G. (Clinical neurophysiology, 2005)
Though vagus nerve stimulation (VNS) is an important option in pharmacoresistant epilepsy, its mechanism of action remains unclear. The observation that VNS desynchronised the EEG activity in animals suggested that this mechanism could be involved in VNS antiepileptic effects in humans. Indeed VNS decreases spiking bursts, whereas its effects on the EEG background remain uncertain. The objective of the present study is to investigate how VNS affects local and inter regional syncronization in different frequencies in pharmacoresistent partial epilepsy. Digital recordings acquired in 11 epileptic subjects 1 year and 1 week before VNS surgery were compared with that obtained 1 month and 1 year after VNS activation. Power spectrum and synchronization were then analyzed and compared with an epileptic group of 10 patients treated with AEDs only. VNS decreases the synchronization of theta frequencies ( P<0.01), whereas it increases gamma power spectrum and synchronization (<0.001 and 0.01, respectively). The reduction of theta frequencies and the increase in power spectrum and synchronization of gamma bands can be related to VNS anticonvulsant mechanism. In addition, gamma modulation could also play a seizure-independent role in improving attentional performances. These results suggest that some antiepileptic mechanisms affected by VNS can be modulated by or be the reflection of EEG changes.